Basal Cell Adenoma of Deep Lobe of The Parotid Gland Commonly Misdiagnosed Tumour of Parotid Gland: A Case Report - Yesmin, Kauser; Khyathi, Meghashyam; Rai, A. K; Abidi, S.M Rahber (Journal of Neonatal Surgery, 2025)
Introduction- Basal cell adenoma is an uncommon benign epithelial neoplasm of the salivary glands, accounting for only 1–2% of all such tumours. While it most frequently arises in the parotid gland, it can also develop in the minor salivary glands. Due to its overlapping features with various benign and malignant salivary gland neoplasms, accurate diagnosis can be challenging. Definitive identification typically relies on detailed histopathological analysis. Case Presentation- A 52-year-old female presented with a painless swelling in the right infra-auricular region. Imaging studies revealed a well-circumscribed hypodense mass located within the deep lobe of the right parotid gland, initially suspected to be a pleomorphic adenoma. Fine needle aspiration cytology (FNAC) yielded inconclusive results. As a result, the patient underwent total conservative parotidectomy. Histological evaluation confirmed the diagnosis of basal cell adenoma, revealing cystic spaces containing mucoid material and basaloid epithelial cells arranged in trabecular and tubular configurations. Discussion- Basal cell adenoma was formally recognized as a distinct tumour entity in the 1991 WHO classification of salivary gland tumours. On cytological examination, it may mimic a variety of both benign and malignant neoplasms of salivary and non-salivary origin. The defining histological features include uniform basaloid cells with small, round nuclei, minimal cytoplasm, absence of atypia, and characteristic peripheral palisading. Surgical excision is the treatment of choice, with more extensive resection indicated for certain histological variants such as the membranous type due to a higher risk of recurrence. Conclusion- This case underscores the clinical, radiological, and histopathological characteristics of basal cell adenoma of the parotid gland. Accurate diagnosis through histological assessment is essential for effective management. Timely surgical intervention is critical in ensuring favourable outcomes and minimizing the risk of recurrence.